A Patient with SIADH, Urinary Retention, Constipation, and Bell's Palsy following a Tick Bite. (11th July 2022) - Leone, Mariana; Iqbal, Anwar; Hugo Bonatti, J. R.; Anwar, Samina; Feaga, Catherine
Abstract : Introduction . Lyme disease is the most common vector borne disease in the USA caused by the bacterium Borrelia burgdorferi. If untreated, Lyme disease can cause a variety of secondary symptoms often difficult to interpret. Some of the rare manifestations of Lyme disease include SIADH-like syndrome, enteroparesis, and urinary retention. Case Report . A 69-year-old male presented with anorexia and constipation and was found to have hyponatremia. Several days after admission, Bell's palsy developed and he experienced urinary retention requiring catheterization. Lyme disease was confirmed on serology, and he recalled a rash on his elbow four weeks prior. Ceftriaxone was started and the patient improved; he had multiple bowel movements after receiving laxatives and the Foley catheter was removed; serum sodium normalized with fluid restriction. He was discharged home and was well with symptoms completely resolved at three-month follow-up. Discussion . There should be a high alert of atypical presentation of this common tick bite associated infection. Review of the literature revealed ten similar cases, but only three of these patients were reported to have a combination of SIADH, urinary retention, and enteroparesis.